Updated estimates of the relationship between the business cycle and traffic fatalities - Rune Elvik (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper updates analyses of the relationship between fluctuations of the business cycle and the number of traffic fatalities published in 2015 by the International Transport Forum. Since then, the global recession that started in 2008 has ended and economic growth has returned to most International Transport Forum countries. The paper revisits the affect that declining or stable high rates of unemployment have on traffic fatalities.
Keywords: 330; Verkehrsunfall; Sterblichkeit; Verkehrsverhalten; Konjunktur; OECD-Staaten